Optical phase of recursional hybrid visco ferromagnetic electromagnetic microscale - Körpınar, Talat; Körpınar, Zeliha (Elsevier, 2023)
In this paper, we construct new optical hybrid normalization shapes of Lorentz fields with hybrid frames in ordinary space. Then, we demonstrate some descriptions for hybrid visco ferromagnetic H2magnetic normalized optimistic solidity. We construct a hybrid normalized visco ferromagnetic H2magnetic hybrid visco ferromagnetic microbeam model with a hybrid frame. Finally, we obtain an optical hybrid normalized visco ferromagnetic H2-electrical hybrid visco ferromagnetic microscale beam. (c) 2023 Elsevier B.V. All rights reserved.
Keywords: Optical Recursion; Optical Ferromagnetic Microscale; Flexible Elastic Microscale; Electric Optimistic Density; Triboelectric Nanogenerators; Fiber; Electronics; Equation; Soliton